What future for primary aluminium production in a decarbonizing economy?. (July 2021) - Pedneault, Julien; Majeau-Bettez, Guillaume; Krey, Volker; Margni, Manuele
Highlights: We modelled prospective life cycle impacts of aluminum production sector up to 2100. SSP narratives are leveraged to model technology penetration and grid mix evolution. We forecast global carbon intensities from 8.6 to 18.0 kg CO2 eq/kg as baseline. Majority of improvements result from policy in the energy sector. Absolute sector-wide CO2 reduction is realistic with aggressive policy efforts. Abstract: Aluminium is an energy intensive material with an environmental footprint strongly dependent on the electricity mix consumed by the smelting process. This study models prospective environmental impacts of primary aluminium production according to different integrated assessment modeling scenarios building on Shared Socioeconomic Pathways and their climate change mitigation scenarios. Results project a global average carbon intensity ranging between 8.6 and 18.0 kg CO2 eq/kg in 2100, compared to 18.3 kg CO2 eq/kg at present, that could be further reduced under mitigation scenarios. Co-benefits with other environmental indicators are observed. Scaling aluminium production impacts to the global demand shows total emission between 1250 and 1590 Gt CO2 eq for baseline scenarios by 2050 while absolute decoupling is only achievable with stringent climate policy changing drastically the electricity mix. Achieving larger emission reductions will require circular strategies that go beyond primary material production itself and involve other stakeholders along the aluminium value chain.